The Legislative Role of Women in the Formation of Qanun in DPRA 2014-2019 Period Review from an Islamic Perspective: Peran Legislatif Perempuan Dalam Pembentukan Qanun Di DPRA Periode 2014-2019 Tinjauan Dari Perspektif Islam - Abdullah, Arifin (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
Role is participation in activities both in the institution and in the community. One of the roles and positions of women in the DPRA is in the process of forming Qanun. Qanun is a legal product made by the DPRA together with the governor of Aceh which is regulated in Law no. 11 of 2006 concerning the Government of Aceh. In this case, the formulation of the problem is how the role of women during the sultaniah period until now and how the position of women as long as the woman was involved in the formation with a review of Islamic law. The purpose of this research is to find out and examine how the role of women in the formation of Qanun in the DPRA during their tenure as members of the legislature is to find out the obstacles and opportunities faced by female politicians in forming the Qanun. The author conducts qualitative research using an empirical normative approach, namely legal research regarding the application of normative legal provisions (codification, laws or contracts) in action on every particular legal event that occurs in society. Sources of data taken by the author, through primary data sources and secondary data. The primary data source is through field research, namely by conducting interviews with members of the DPRA. Meanwhile, secondary data sources are through library research, namely documents and lists of related reading books. The results of the research carried out by the author are that the role of women in the process of forming the qanun is only as a member who proposes, gives opinions and critiques, it is rare for a woman to be the chairman when drafting the qanun, in Islam women are only as input providers who decide, namely Rasulullah as in the Hudaibiyah agreement.